A local quality initiative to improve follow-up times for patients with heart failure. Issue 2 (24th September 2017) - Schofield, Toni; Duero Posada, Juan; Foroutan, Farid; Alba, Ana Carolina; McDonald, Michael; Linghorne, Meredith
Abstract : Introduction Heart failure is the most common cause of hospital admission in patients >65 years and around 50% of patients will be readmitted within 6 months. Inability to achieve timely outpatient follow-up may contribute to the high rates of avoidable rehospitalisation for this group of patients. Canadian guidelines recommend patients with heart failure should be seen within 14 days of discharge. Methods An audit demonstrated that less than half of advanced heart failure patients were being followed up within 14 days. In an effort to improve postdischarge follow-up in our heart function clinic, we used process mapping and applied a series of iterative changes to the appointment booking system using Plan–Do–Study–Act cycles to reduce waste and standardise. Results The primary outcome measure, tracked over a period of 20 months, was percentage of patients booked within 14 days. At baseline, 37% of patients were seen within 14 days. After our series of interventions related to streamlining and standardising the appointment booking process, 77% of patients were seen within 14 days and 100% of patients were seen within 21 days. Conclusion The changes made to the appointment booking process were reproducible, sustainable, effective and required no additional resources or funding.